2007
DOI: 10.1038/sj.emboj.7601678
|View full text |Cite
|
Sign up to set email alerts
|

A novel ISWI is involved in VSG expression site downregulation in African trypanosomes

Abstract: African trypanosomes show monoallelic expression of one of about 20 telomeric variant surface glycoprotein (VSG) gene-expression sites (ESs) while multiplying in the mammalian bloodstream. We screened for genes involved in ES silencing using flow cytometry and RNA interference (RNAi). We show that a novel member of the ISWI family of SWI2/SNF2-related chromatin-remodelling proteins (TbISWI) is involved in ES downregulation in Trypanosoma brucei. TbISWI has an atypical protein architecture for an ISWI, as it la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 48 publications
5
139
0
Order By: Relevance
“…The precise underlying molecular mechanism is still not understood. Although several molecular players have been shown to be involved (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), depletion of any of these factors had only a moderate effect on the repression of silent VSG genes. Therefore, either a master regulator is still to be discovered or, alternatively, the process is controlled by multiple collaborative factors ensuring a cumulative tight lock.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise underlying molecular mechanism is still not understood. Although several molecular players have been shown to be involved (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), depletion of any of these factors had only a moderate effect on the repression of silent VSG genes. Therefore, either a master regulator is still to be discovered or, alternatively, the process is controlled by multiple collaborative factors ensuring a cumulative tight lock.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the level at which the control takes place is unknown: Whether the transcription control takes place at the initiation or elongation level is debated. Data reporting low levels of transcripts from silent ESs upon RNAi-mediated knockdown of various factors (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) cannot resolve this issue, because the data are compatible with both models. Previous experiments pointed to mixed conclusions.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The active B-ES has very few nucleosomes while silent ESs are packed with nucleosomes (Figueiredo & Cross 2010;Stanne & Rudenko 2010). A number of studies also showed that chromatin remodeling plays an important role, particularly in regulating the B-ES promoter activity: Depletion of a Swi/Snf homolog, TbISWI, led to an elevated transcription from the silent ES promoters, although VSG expression is not affected (Hughes et al 2007;Stanne et al 2011); Deletion of the histone H3K79 methyltransferase TbDot1b led to a 10-fold increase in transcription throughout the silent ESs (Janzen et al 2006); Of the three T. brucei histone deacetylase homologs, DAC3 is required for B-ES promoter silencing at both BF and PF stages, and DAC1 antagonizes basal telomeric silencing in BF cells without affecting B-ES transcription (Wang et al 2010); And depletion of TbSpt16, a subunit of the FACT chromatin remodeling complex, also led to an ~20-fold increase in silent B-ES promoter transcription in both BF and PF cells (Denninger et al 2010). Third, ever since the discovery that VSGs are exclusively expressed from subtelomeric regions (de Lange & Borst 1982), it has been proposed that telomeres may play an important role in VSG expression regulation (Dreesen et al 2007).…”
Section: Rap1-mediated Silencing Is Essential For Monoallelic Expressmentioning
confidence: 99%
“…Mol Biol Evol 21: 1620-1624. Aitcheson, N.; Talbot, S.; Shapiro, J.; Hughes, K.;Adkin, C. et al 2005. VSG switching in Trypanosoma brucei: antigenic variation analysed using RNAi in the absence of immune selection.…”
Section: Referencesmentioning
confidence: 99%